O7: APPARENT PATHOLOGICAL COMPLETE RESPONSE TO NEOADJUVANT THERAPY LEADS TO SELECTION OF TREATMENT RESISTANT CANCER STEM CELLS IN OESOPHAGEAL ADENOCARCINOMA. (27th April 2021) - Walker, RC; Harrington, J; Grace, B; Lloyd, M; Byrne, JP; Kelly, JJ; Noble, F; Rose‐Zerilli, MJ; Underwood, TJ
Abstract: Introduction: In oesophageal adenocarcinoma with an apparent pathological complete response (pCR) to neoadjuvant therapy (NAT) there remains debate as to whether oesophagectomy is required. Single Cell RNA sequencing (scRNAseq) enables identification and characterisation of cell populations at higher resolution than diagnostic techniques. Method: ScRNAseq was used to determine transcriptomic profiles of cell populations in 24 OAC tumours and 13 matched normal samples. Five were also analysed using bulk RNA sequencing and high‐precision mass spectrometry proteomics. Immunohistochemistry (IHC) was used to validate pCR. Paired scRNAseq analysis of pre‐and post‐treatment specimens from three further patients was used to compare transcriptomic profiles before and after NAT. Cancer cells (CCs) were assigned a cancer stem cell (CSC) score curated from published gene sets. Result: We analysed a total of 22, 738 single cells forming 29 different cell phenotypes. In two samples with apparent pCR, IHC staining, bulk RNA sequencing and proteomics of post‐treatment samples failed to identify CCs. ScRNAseq, conversely, revealed persistent CCs (12/978 and 45/774). Transcriptomic analysis identified upregulation of stem cell markers and high CSC scores in these cells. Conclusion: We have shown that CCs persist beneath the lower detection limit of standard approaches in apparent pCR. These cells express marker genes and expression programs consistent with CSCs. CSCs are a critical subpopulation that drive tumour initiation, growth, invasion, metastasis and resistance to therapy. These gene expression programs are not enriched in non‐responders and straight to surgery samples. Oesophagus sparing treatment algorithms in pCR may subject patients to unnecessary risk of progression. Take‐home message: Cancer cells remain within tumours after apparent complete pathological response. These cells express stem cell markers associated with resistance to therapy and cancer progression.